DC motor control using LQR algorithm - Adezeno, Sagoli Olid (2008)
A real-time control is an approach to evaluate a control system with a real time parameters or weighting factors. The recent demand of stability and better performance in industries has led researchers to do intensive development to come out with methodologies to enhance the performance control system. A control system is a device or set of devices to manage, command, direct or regulate the behavior of other devices or systems. In this research, the predictive algorithm namely Linear Quadratic Regulator (LQR) will be design along with the industries certified DC motor in order to monitor the peak performance of the system and the stability of the design after interfacing with Programmable Logic Controller (PLC). An application in Matlab called Simulink is used as tools for algorithm implementation. Simulink is chosen due to its block diagram implementation and its creation of user interface which allowing interfacing with programs in others languages. Hence it is essential for complex algorithm to control real time process system. Programmable Logic Controller (PLC) is known as process models by industries for several years. As in this project, the LQR controller will be develop in the PLC in order to control the DC motor running at optimum speed. The LQR controller will act as a benchmark for the algorithm performance of the overall control system.